Nuchal translucency audit: a novel image‐scoring method - Herman, A.; Maymon, R.; Dreazen, E.; Caspi, E.; Bukovsky, I.; Weinraub, Z. (Ultrasound in obstetrics & gynecology, 1998)
Objective The aim of this study was to evaluate the feasibility and reproducibility of a novel image‐scoring method of first‐trimester nuchal translucency measurement as an objective tool of ongoing audit and training. Design This was an independent evaluation of nuchal translucency images by three separate reviewers unaware of the examiner. Subjects There were 105 consecutive singleton pregnancies undergoing first‐trimester screening. Methods Each image was scored according to the following criteria: section (oblique, 0; mid‐sagittal, 2), caliper placing (misplaced, 0; proper, 2), skin line (nuchal only, 0; nuchal and back, 2), image size (unsatisfactory, 0; satisfactory, 1), amnion (not visualized, 0; visualized, 1) and head position (flexion/hyperextension, 0; straight, 1). The final score was categorized into one of four quality groups: excellent (8–9), reasonable (4–7), intermediate (2–3), unacceptable (0–1). Results The distributions of the four quality groups were similar between the three reviewers: 11.4% were classified as excellent, 57.1% as reasonable, 25.7% as intermediate and 5.7% as unacceptable. Inter‐reviewer agreement showed identical classification, by each pair of reviewers, from 65.7% to 74.3%, and partial agreement to neighboring quality groups from 25.7% to 34.3% of the cases. In none of the cases did the reviewers differ in categorizing cases to remarkably different quality groups. Application of the auditing method to the examiners showed similar distribution to the various quality groups and similar mean final score of 4.69 (0.39, SE), 4.54 (0.15, SE) and 4.65 (0.15, SE). Conclusions The described image‐scoring method represents a new approach towards the evaluation of ultrasound performance as a whole and nuchal translucency measurement in particular. It may be employed by every center in an independent manner with minimal resources and regardless of the method of risk assessment. More studies will be needed to determine the standards required from the examiners and to elucidate the contribution of the proposed auditing method to the examination's quality and the process of training. Copyright © 1998 International Society of Ultrasound in Obstetrics and Gynecology